An Occupation-Based Clinic Makeover: Perceptions and Experiences of Occupational Therapists - Wendy B. Stav; Alison R. Herman (Scholarworks @ WMU, 2022)
Background: Researchers sought to discover the experiences of occupational therapists transitioning from existing clinical practice to exclusively occupation-based approaches. Method: This phenomenological study captured the experiences of clinicians as exercise-based equipment was temporarily removed from the rehabilitation gym and replaced with occupation-based kits. The therapists used the new occupation-based materials with all clients for 4 months and participated in interviews and a focus group. Results: The study yielded a greater understanding therapists' process and experiences through the themes: (a) challenges to occupation-based practice and (b) occupation-based metamorphosis. Conclusions: The personal and contextual obstacles associated with implementing occupation-based practice hinder occupational therapists' abilities to practice aligned with the profession's philosophical beliefs. However, when sufficient supports are in place, therapists traverse the "change curve" and ultimately experience a professional evolution into an occupation-centered paradigm.